Attitudes of young patients with breast cancer toward fertility loss related to adjuvant systemic therapies. EORTC study 10002 BIG 3‐98†. Issue 2 (29th August 2013) - Senkus, Elżbieta; Gomez, Henry; Dirix, Luc; Jerusalem, Guy; Murray, Elizabeth; Van Tienhoven, Geertjan; Westenberg, A. Helen; Bottomley, Andrew; Rapion, Jérôme; Bogaerts, Jan; Di Leo, Angelo; Nešković‐Konstantinović, Zora
Abstract Objective Infertility due to anticancer treatments is a major source of distress for young patients with cancer. A survey was performed among breast cancer patients younger than 35 years, to evaluate the acceptance of chemotherapy in the context of infertility risk. Methods After obtaining written informed consent, we asked 400 premenopausal, early stage breast cancer patients aged ≤35 years to complete a short, previously pilot‐tested questionnaire. Three hundred and eighty‐nine patients were evaluable. The association between the explanatory variables and the outcome variables was assessed using logistic regression. Results Two hundred and twenty‐eight (59%) participants wanted to have (more) children in the future, whereas 158 (41%) did not. Fifty‐seven (36%) of the latter did not want additional children because of fear of cancer recurrence. Thirty‐two women (8%) stated they would not accept chemotherapy should it reduce their fertility. This was dependent upon already having children, the wish to have (further) children, geographical area, disease stage, and already planned chemotherapy. One hundred and seventy‐one women who would agree to chemotherapy (48%) would accept a risk of infertility of 76–100%. This acceptance was dependent on already having children and the wish to have (more) children. Of the 355 participants (91%) accepting chemotherapy, 48 would accept it only for ≥20% gain in cure. Conclusion For the majority of young patients with breast cancer, cure remains their first priority; for this, they are willing to accept a considerable decrease in future fertility, and only less than 10% will forego chances of cure to preserve fertility. Copyright © 2013 John Wiley & Sons, Ltd.